Co-application of Arbuscular Mycorrhizae via Seed Coating and Phosphorus Fertilizer for Enhancing Growth, Yield, and Nutrient Uptake in Ultisols for Maize - Marwanto, Marwanto; Bustamam, Hendri; Handajaningsih, Merakati; Anggraini, Septiana (BPFP Universitas Bengkulu, 2024)
A field trial was conducted to determine the efficiency of AMF inoculation for enhancing growth and yield performance of maize, root colonization, soil available P, and P uptake in Ultisols amended with different P dosages. This experiment was conducted in a 3 x 3 factorial scheme under complete randomized design with three AMF inoculation methods and three different P levels (0, 60, and 120 kg P2O5 ha-1) in five replications. Data were collected on plant growth, yield parameters, soil available P, P uptake, and root colonization. Results showed that inoculation via seed coating at 60 kg P2O5 ha-1 gave a significant (p<0.05) increase in growth traits (average of 25%), biomass production, grain yield (average of 30%), soil P availability, P uptake, and root colonization. Inoculation via seed coating combined with 60 produced the same values of all the tested parameters with and seed coating inoculation and soil inoculation at120 kg P2O5 ha-1. Thus, seed coating was as effective tool as soil inoculation for AMF delivery and capable of reducing 50% of P fertilizer use. For these reasons, co-application of P fertilizer and AMF inoculation via seed coating could be practiced to improve corn yields on poor Ultisols.